PREPARASI, KARAKTERISASI, DAN UJI AKTIVITAS KATALIS NI-MO/ZEOLIT ALAM DALAM PROSES CATALYTIC CRACKING JELANTAH MENJADI BIOGASOLINE (Universitas Negeri Semarang, 2012)
Research about preparation, characterization, and activity test of Ni-Mo/ZA catalyst on catalytic cracking process of used cooking oil has been done. The variables studied during the activity test were hydrogen flow rate and reaction temperature. The type of condensate products result of cracking process was also studied. Characteristics of the Ni-Mo/ZA catalyst including metal content of Ni and Mo,acidity, and porosity of catalyst were determined by Atomic Adsorption Spectroscopy (AAS), gravimetric method, and BET method respectively. The waste cooking oil was firstly reacted with base KOH and methanol to produce methyl ester waste cooking oil. The process of catalytic cracking waste cooking oil with Ni-Mo/ZA catalysts carried out for 1.5 hours by varying the temperature of 300oC, 350oC, and 400oC, and varying the hydrogen flow rate of 10, 20, 30, 40, and 50 mL/min. The products were analyzed by means Gas Chromatography and Gas Chromatography-Mass Spectroscopy. It is shown that the highest conversion percentage of 53.4% reached at the optimum temperature of 350oC, whereas optimum hydrogen flow rate obtained at 20 mL/min. It is also shown that the composition of product consisted of hexane 89.58%, cyclopentane 3.44%, pentane 3.03%, 2-propanone 0.94% and octane 0.07%.